Recycled Polypropylene/Kenaf Fiber/Halloysite (rPP/rNR/KF/Hall) smart composites: The influence of bio-compatibilizer addition on Tensile, Morphological and Heat Combustion Properties. (September 2019) - Suharty, N S; Ismail, H; Diharjo, K; Handayani, D S; Sholihati, A; Nisa', A I
Abstract: Had been successfully synthesized rPP/DVB/PP-AA/rNR/KF//Hall+ZB smart composite in solution reactive processes with various recycled Natural Rubber (rNR) bio-compatibilizer concentration. The addition of rNR bio-compatibilizer improved the total capacity loading (Hall and KF) filler to reach the optimum concentration. The addition of 3% rNR is capable to increase capacity of total loading filler KF and Hall up to 46% as the optimum condition (KH4). At optimum conditions it can increase the Tensile Strength (TS) and Elongation (Elo) up to 16% and 17% respectively, and decrease the Young Modulus (YM) to 1% compared to that the composites without rNR (KH1). The rNR plasticizer serves as a bio-compatibilizer that can increase the loading filler capacity and well interaction, finally, it can increase the TS properties. The increase of total loading filler KF and Hall to 46% (KH4) can also improve the inflammability of the composites. The Heat combustion (Hg) of KH1 without rNR was 42.3 kJ/g and at optimum condition the Hg of KH4 increases 4.8%, compared to that of KH1. The time to Ignition (TTI) increases by 6.9%, Burning Rate (BR) decreases by 3.7% and the Heat Release (HR) increases by 2.1% compared to that of the composites without rNR (KH1).